Crystal structure of dichlorido-bis(4-chlorophenyl-κC1)tin(IV), C12H8Cl4Sn - Lo, Kong Mun *; Lee, See Mun *; Tiekink, Edward R. T. * (De Gruyter Open, 2021)
C12H8Cl4Sn, monoclinic, P21/c (no. 14), a = 13.4238(1) Å, b = 18.2079(2) Å, c = 5.7617(1) Å, β = 95.506(1)°, V = 1401.77(3) Å3 , Z = 4, Rgt(F) = 0.0272,wRref(F2) = 0.0798, T = 100 K.